2022
DOI: 10.3389/fncel.2022.882306
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Exosomes and Exosomal Noncoding RNAs From Different Cell Sources in Spinal Cord Injury

Abstract: Spinal cord injury (SCI) not only affects the quality of life of patients but also poses a heavy burden on their families. Therefore, it is essential to prevent the occurrence of SCI; for unpreventable SCI, it is critical to develop effective treatments. In recent years, various major breakthroughs have been made in cell therapy to protect and regenerate the damaged spinal cord via various mechanisms such as immune regulation, paracrine signaling, extracellular matrix (ECM) modification, and lost cell replacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 146 publications
(169 reference statements)
0
4
0
Order By: Relevance
“…In this context, studies were conducted on the use of EVs as carriers of biomolecules that can efficiently deliver Tf, protecting the cargo from degradation while reducing immunogenicity (Haney et al, 2015; Luan et al, 2017; Wiklander et al, 2015; Yang et al, 2022). In previous work, we employed two passive cargo‐loading strategies which rendered successful EV loading with Tf, specifically through binding to its receptor TfR1, present in the EV membrane (Mattera et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, studies were conducted on the use of EVs as carriers of biomolecules that can efficiently deliver Tf, protecting the cargo from degradation while reducing immunogenicity (Haney et al, 2015; Luan et al, 2017; Wiklander et al, 2015; Yang et al, 2022). In previous work, we employed two passive cargo‐loading strategies which rendered successful EV loading with Tf, specifically through binding to its receptor TfR1, present in the EV membrane (Mattera et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes, the smallest extracellular membranous vesicles (~30-150 nm), contain nucleic acids (e.g., DNA, mRNA, noncoding RNA), proteins (e.g., CD63/CD81/CD9, HSP60/HSP70/HSPA5/CCT2/ HSP90, TSG101, AIP1/ALIX), and lipids (e.g., cholesterol, phosphatidylserine, phosphatidylinositol), suggesting a critical role in cell-cell communication [87]. NSPC-secreted exosomes (SC-Exos) can exert neurogenic, neurotrophic, anti-apoptotic, and anti-inflammatory effects while avoiding the limitations of the original stem cells, such as tumorigenicity, thrombogenicity, and immunogenicity [88]. A retrospective study based on animal SCI models indicated that SC-Exos derived from different stem cells increased the expression of anti-inflammatory factors (IL-4, IL-10) and anti-apoptotic protein Bcl-2, and reduced the levels of pro-inflammatory factors (IL-1β, TNF-α) and apoptotic protein BAX, thus improving the motor function recovery [89].…”
Section: Stem Cell-derived Exosome Administrationmentioning
confidence: 99%
“…Cell therapy has made breakthroughs in the treatment of SCI in recent years. However, due to its tumorigenicity and low survival rate at the time of treatment, it still has some limitations in clinical application [46]. Exosome-mediated therapy can inhibit the synthesis of some proteins in the body that prevent SCI recovery and promote the regeneration of some cells to restore body function.…”
Section: Exosomes In Spinal Cord Injury (Sci)mentioning
confidence: 99%